Hedonism in tafsir al-azhar: A Paul Ricoeur hermeneutic analysis and its implications for moral communication in muslim societies - Chairunnisa, Nadya Syafa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In the modern era, the rise of consumptive and materialistic lifestyles has shaped a new form of hedonism that challenges moral and spiritual values in religious teachings. Islam, through the Qur'an, offers a comprehensive view of life. This study aims to analyze the concept of hedonism in the Qur'an through Hamka's Tafsir Al-Azhar using Paul Ricoeur's hermeneutical approach. A number of previous studies have discussed hedonism from a philosophical or sociological perspective, but not many have examined it through a hermeneutic reading of Islamic texts. Methods: This research is classified as qualitative research. The primary data source used is the book Tafsir Al-Azhar. Supporting data includes articles, journals, books related to hedonism, and scientific books. The data collection technique used is the library research method. The data analysis used is descriptive analysis and also uses the mauḍū'I (thematic) interpretation method. Findings: The results of this study are as follows, a) an excessive love for the world, as found in QS. Al-Imran verse 14, b) the attitude of squandering wealth, as found in QS. Al-Qashash verse 77, c) the attitude of being wasteful and extravagant, as found in QS. Al-Isra verse 27. Conclusion: Its relevance to Indonesian society is evident in cases of corruption, where many people, especially young people, buy things not because they need them, and many people will do anything, even if it is wrong, to fulfill their hedonistic lifestyle. Novelty/Originality of this article: From several literature reviews that have been described, there has been no specific research related to the theme of hedonism in the Al-Azhar book. Therefore, this research is important to investigate.